Pengembangan Media Layanan Informasi Untuk Meningkatkan Minat Belajar Peserta Didik di SMP Negeri 1 Batang Anai - Vio Marlina; Triyono Triyono; Yasrial Chandra (Universitas PGRI SUMATERA BARAT, 2022)
This research is motivated by the existence of students who have low interest in learning and there are still teachers who are not able to use media in the learning process. This study aims to 1) describe students' interest in learning at SMP Negeri 1 Batang Anai 2) Validate information service media to increase student learning interest which is theoretically acceptable.This type of research is research and development. The steps of this research the researcher limits 5 development steps, namely (1) potential and problems, (2) data collection, (3) product design, (4) design validation (validated by 3 examiners), (5) design revision . The population of this study were students of class VIII at SMP Negeri 1 Btang Anai totaling 256 people with a sample of 72 people who were selected using proportional random sampling technique. The research data was obtained through a questionnaire and processed using the percentage technique. Based on the results of the study revealed that: 1). In general, there were 38 students (53%) in the medium category. 2) after the media testing was carried out on three validators namely Mrs. Dr. Helma, M.Pd, Mr. Mori Dianto.M.Pd, and Mr. Suryadi M.Pd. with an average score of 3.49 in the category of very acceptable theoretically and feasible to be used to increase student interest in learning